Cellular and molecular modulation of rotator cuff muscle pathophysiology. Issue 11 (30th September 2021) - Fu, Chengcheng; Huang, Alice H.; Galatz, Leesa M.; Han, Woojin M.
Abstract: Rotator cuff (RC) tendon tears are common shoulder injuries that result in irreversible and persistent degeneration of the associated muscles, which is characterized by severe inflammation, atrophy, fibrosis, and fatty infiltration. Although RC muscle degeneration strongly dictates the overall clinical outcomes, strategies to stimulate RC muscle regeneration have largely been overlooked to date. In this review, we highlight the current understanding of the cellular processes that coordinate muscle regeneration, and the roles of muscle resident cells, including immune cells, fibroadipogenic progenitors, and muscle satellite cells in the pathophysiologic regulation of RC muscles following injury. This review also provides perspectives for potential therapies to alleviate the hallmarks of RC muscle degeneration to address current limitations in postsurgical recovery.